Explaining city branding practices in China's three mega-city regions: The role of ecological modernization. (1st April 2018) - de Jong, Martin; Chen, Yawei; Joss, Simon; Lu, Haiyan; Zhao, Miaoxi; Yang, Qihui; Zhang, Chaoning
Abstract: As global cities, Hong Kong, Shanghai and Beijing operate in international economic networks; however, they are also each firmly embedded within a regional context and are surrounded by less populous and less internationally recognized neighbors. Together they form so-called mega-city regions referred to as the Greater Pearl River Delta, the Yangtze River Delta, and the Bohai Rim, each encompassing a dozen or so cities. In the wake of staggering economic growth and threatening pollution, these cities are compelled to respond to the challenge of ecological modernization (EM): aim for higher economic value added at lower environmental cost. Cities have particular industrial and regional profiles; consequently they follow different developmental pathways. In order to attract coveted investors, green and high-tech corporations, well-endowed residents and talented workforce, these cities engage in city branding practices. In this contribution, a typology of EM developmental pathways is presented and the 41 cities in the three Chinese mega-city regions are analyzed in terms of their respective pathways and city branding practices. We argue that different industrial and regional profiles allow for different developmental pathways making different city branding strategies likely. Most cities brand themselves in comformity with what their pathway would lead us to predict, except cities with a strongly manufacturing oriented profile; the brands of the latter type deviate markedly from their current reality. Cities adopting branding strategies that contrast sharply with their historical legacy and current profile risk promoting themselves in ways that the outside world is likely to perceive as lacking in credibility. Highlights: First to identify the impact of industrial developmental pathways and regional positions on city branding. Relates branding practices adopted by cities to five Ecological Modernization (EM)-related developmental pathways. Operationalizes city branding practices through (1) city brand identities and (2) city labels. Applies this framework to all cities in the three Chinese mega-city regions Bohai Rim, Yangtze River Delta and Greater Pearl River Delta. Finds that for pathway 2 (advanced manufacturing), cities brand themselves differently than expected from their economic and geographic profiles.